EFFECT OF LIGNOSULFONATE CONTENT ON THE ADHESIVE STRENGTH AT VENEERING OF MEDIUM DENSITY FIBREBOARDS - Savov, Viktor; Angelski, Dimitar (Innovation in Woodworking Industry and Engineering design, 2022)
The transition to a circular bio-oriented industry requires the search for alternative raw materials, sources and binders in producing materials for the furniture industry.Lignosulfonates (sulphite lignins) are by-products, residues, of cellulose production, and they are bio-based materials with adhesive properties.This work presents a study evaluating lignosulfonates as binders in the veneering of Medium Density Fibreboards (MDF). An adhesive composition of urea-formaldehyde (UF) resin and ammonium lignosulfonate was used in the veneering. Preliminary experiments have been carried out that show a significant reduction in the adhesion strength when the lignosulfonate content in the adhesive system passes 60%. Therefore, the study used the substitution of UF resin with lignosulfonate from 0 to 60%, with a step of variation from 10%. It is carried out at the gelling time of the various adhesive systems.An analysis of the adhesive strength in veneering at adhesive systems with different lignosulfonate content was performed. Based on this, conclusions and recommendations were derived.